The Rule of “Business with the Affinities” is an Original Study - Al-Badarin , Ayman (Islamic Sciences Journal, 2023)
The study was keen to collect the origins of “intention” in Islamic law, jurisprudence and principles through the rooting of the prophetic rule (actions by intentions). The intention for it, the place of the intention, the rule of its pronunciation, the intention between the corner and the conditional, and its time, and the conditions of the rule by clarifying the conditions of the intention and the intention and the intended action, and what needs the intention of actions, then the study concluded with a statement of the most prominent results of the research and its recommendations.